Efek Moderasi Kebijakan Dividen Pada Pengaruh Tax Avoidance Terhadap Nilai Perusahaan: (Studi Empiris Perusahaan Indeks LQ45 di BEI periode 2016-2020) - Prasetyo Saputra (Yayasan Literasi Ilmiah Indonesia, 2023)
Purpose: This research is motivated by investment trends and the increasing number of investors in Indonesia. The purpose of this study is to determine the moderating effect of dividend policy on the effect of tax avoidance on firm value. Tax avoidance is a tax avoidance activity carried out by companies as a form of tax management. Then, it will affect investment decisions and assessment of the feasibility of the company by investors to invest their capital. Method: Using data analysis with 85 samples of financial statements of LQ45 index companies listed on the Indonesia Stock Exchange 2016-2020. The sample selection technique uses purposive sampling technique with moderated regression analysis (MRA). Data collection method through the official IDX website: www.idx.co.id. Finding: The results prove that tax avoidance has a positive effect on firm value. The moderating effect of dividend policy is proven to strengthen the effect of tax avoidance on firm value. This can happen because the results of tax avoidance carried out by the company are considered to be diverted to investment capital or as dividend payments to investors. Novelty: As a proxy for calculating dividends, the current study uses a dummy variable, as opposed to the dividend payout ratio (DPR) used in earlier studies.